Efektivitas Penyelesaian Sengketa Hasil Pemilihan Umum oleh Mahkamah Konstitusi dalam Menanggapi Batas Waktu dan Banyaknya Perkara - Pitaloka, Putri Galuh; Hadi, Rival Mahesa Fauzan; Sembiring, Nirindah Daniella; Tampubolon, Toby Samuel; Marsal, Irsyaf (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The handling of election result disputes by the Constitutional Court is a crucial part of maintaining the integrity and legitimacy of the democratic process in Indonesia. The dispute resolution mechanism has been regulated in detail in laws and regulations, including the Constitutional Court Law and other technical regulations. This procedure includes the stages of filing an application, preliminary examination, evidence, and a final and binding decision, with the principle of legal certainty and substantive justice as the main foundation. The effectiveness of the Constitutional Court in resolving election result disputes is highly dependent on its ability to comply with the time limit set by law, namely 14 working days since the application is recorded in the Constitutional Case Registration Book (BRPK). This study shows that in general the Constitutional Court has been able to resolve cases within the specified time, although there are challenges related to limited examination time and the complexity of the cases. Compliance with this time limit demonstrates the professionalism of the Constitutional Court, but also requires optimal administrative and human resource readiness. In facing the surge in the number of cases, especially in simultaneous elections, the Constitutional Court faces a major challenge in maintaining efficiency without ignoring the principle of justice. The strategies implemented include strengthening the case management system, using information technology, and a collective collegial approach in decision-making. Although the high workload may affect the depth of analysis, the Constitutional Court strives to maintain the quality of its decisions by maintaining independence and objectivity. Thus, the Constitutional Court plays an important role in responding to the dynamics of electoral democracy quickly, fairly, and constitutionally